Impacts of Early Life Stress on the Methylome and Transcriptome of Atlantic Salmon - Moghadam, Hooman; Johnsen, Hanne; Robinson, Nick; Andersen, Øivind; Jørgensen, Even Hjalmar; Johnsen, Helge K.; Bæhr, Vegar J.; Tveiten, Helge (Scientific Reports, 2017)
Source at http://dx.doi.org/10.1038/s41598-017-05222-2 Exposure to environmental stressors during early-life stages can change the rate and timing of various developmental processes. Epigenetic marks affecting transcriptional regulation can be altered by such environmental stimuli. To assess how stress might affect the methylome and transcriptome in salmon, fish were treated using cold-shock and air-exposure from the eye-stage until start-feeding. The fish were either stressed prior to hatching (E), post-hatching (PH), pre- and post-hatching (EPH) or not stressed (CO). Assessing transcriptional abundances just prior to start feeding, E and PH individuals were found to have modified the expression of thousands of genes, many with important functions in developmental processes. The EPH individuals however, showed expression similar to those of CO, suggesting an adaptive response to extended periods of stress. The methylome of stressed individuals differed from that of the CO, suggesting the importance of environment in shaping methylation signatures. Through integration of methylation with transcription, we identified bases with potential regulatory functions, some 10s of kb away from the targeted genes. We then followed fish growth for an additional year. Individuals in EPH showed superior growth compared to other treatment groups, highlighting how stress can potentially have long-lasting effects on an organism’s ability to adapt to environmental perturbations.